De mãe para filha: um estudo sobre a transmissão intergeracional dos significados atribuídos pelas mulheres judias à sexualidade feminina - Setton, Marcia Zalcman (2008)
This study is concerned to a comprehension of the transmission process of the meanings attributed to feminine sexuality by Jewish mothers to their daughters, considering that this theme is one of the main propulsive points of social changes on the twentieth century. The guide question of this work is how this woman, who lived and is still living this whole transformation is getting to integrate the social changes and what is transmitted to the new generation: if there are modifications and of what type, in the education that these women could provide to their daughters in the sexuality area. To achieve this general purpose, a qualitative research was made, based on the new paradigmatic systemic assumptions, which specific aims were: comprehend what values and beliefs about sexuality the actual mothers received from their own mothers; how this transmission was made; what values and beliefs about sexuality theses mothers are transmitting to their daughters; in what manner this transmission is done; what values and beliefs the daughters have and how they intend to transmit to their own daughters; how these values and beliefs help in the construction of the femininity sense to these women. There have been made semi-structured interviews with women of the Jewish Community, between 45 and 55 years old and their respective daughters, between 20 and 30 years old, six secular pairs of mother and daughter and two orthodox pairs, in order to observe the difference of groups more closed to traditions and groups more integrated to the general society. These mothers are women that lived their youth on the seventeenth decade and received a traditional education, based in the cultural and social desirable stereotypes for them, but that lived during the sexual revolution, that means, a rupture in the beliefs, values and patterns of learned behaviors. As a result it was possible to observe a great influence from the social and cultural changes in the transmission of the meanings from mother to daughter, although it was noted a repetition of the familiar patterns. However, these changes weren t uniforms, varying in according with the history, beliefs, values and behaviors of each family. The secular families looked for, each one in his measure, to be opened for new reflexions to the new demands, while the orthodox needed to develop a whole range of specific resources to have their traditions survival granted. It was also observed a great women difficulty to have the autonomy preconized by the speech of the sexual revolution incorporated in their personal lives. Only one of the women interviewed crossed this limit, confronting a lot of resistance in her familiar and social life. It is important to have this in mind for the professional that is going to receive this contemporaneous woman in his clinic, in ethics parameters, to accept the other as a legitimized other, and from this base, build with her new possibilities